2020
DOI: 10.1186/s12909-020-02188-0
|View full text |Cite
|
Sign up to set email alerts
|

Competence of pharmacy mentors: a survey of the perceptions of pharmacy postgraduates and their mentors

Abstract: Background: Although mentorship can bring many benefits to medical education, mentors' need for professional development is typically ignored. This study aims to acquire insight into the development of pharmacy mentors' competence by comparing differences between mentors' and postgraduates' perspectives. Methods: We used ANOVAs, independent-sample T-tests and paired-sample T-tests to analyze data collected via an anonymous survey, which included a prepared questionnaire completed by 118 pharmacy mentors and 11… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Management. For data samples of the big data in the database for the sports competition management behavior characteristics [13][14][15], the statistical characteristics of the sports competition management behaviors are analyzed. Firstly, the variables are determined.…”
Section: Analysis Of Education Data On Sports Competitionmentioning
confidence: 99%
“…Management. For data samples of the big data in the database for the sports competition management behavior characteristics [13][14][15], the statistical characteristics of the sports competition management behaviors are analyzed. Firstly, the variables are determined.…”
Section: Analysis Of Education Data On Sports Competitionmentioning
confidence: 99%
“…29 Several studies reported that mentoring in experiential education is significant for the advancement of pharmacy practice, intending to develop highly competent pharmacists that will serve to optimize therapeutic plans and foster patient care through effective interprofessional collaboration within the healthcare team, which is in agreement with our findings. 19,20,30 Additionally, students reported that mentors should be matched with mentees based on same values and/or interests, and not gender. The Lebanese population is very diverse regarding the various religions practiced, however the students reported that religion is not a significant factor to pair a mentor to a mentee.…”
Section: Discussionmentioning
confidence: 99%
“…Yue et al and Engle et al pointed out that professionalism requires exhibiting the highest standards of integrity, honesty, objectivity, and respect when dealing with patients which is consistent with our findings. 19,20 Training students to deal with challenges in practice enhances their problem-solving and critical thinking skills. All these skills and their significance in experiential education illustrate the crucial role clinical mentors exhibit in training students during their pharmacy practice experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a virtual environment created by digital technology [1][2], virtual reality (VR) is a virtual situation and an imaginary world not existing in the real world, and also brings customers multiple sensory experiences such as sight, sound, touch and smell.It offers brand-new 3D perceptual experiences [3][4] to customers, who can experience the virtual world through display or data glove tools [5].Multimedia image edge detection computing creates a novel visual world for customers, and this approach is currently applied to several fields and is a new development trend.Conventional forms of viewing are experienced by the audience following the camera, and the director controls the creation of works.Totally different from the conventional viewing form (passive reception of information), multimedia imagesare a game-changer (active reception), and the audience no longer needs to experience by following the camera. Instead, they can justgo by favorite free conversion, so everyone's visual perception and experience of the impact of VR is different.…”
Section: Introductionmentioning
confidence: 99%